2017
DOI: 10.1097/qad.0000000000001481
|View full text |Cite
|
Sign up to set email alerts
|

Plasma dickkopf-related protein 1, an antagonist of the Wnt pathway, is associated with HIV-associated neurocognitive impairment

Abstract: Objective DKK1 is a soluble antagonist of the Wnt pathway. It binds to and sequesters LRP5/6 away from Wnts. Because the Wnt pathway regulates synaptic transmission and plasticity, we hypothesized that increased DKK1 would increase the risk for neurocognitive impairment (NCI) in HIV+ individuals. We evaluated here the relationship between plasma DKK1 and global NCI. Methods Plasma samples and data from 41 HIV+ and 42 HIV− adults were obtained from the University of California, San Diego. Concentrations of DK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…The Dickkopf-related protein 1 (DKK1) is a secreted soluble antagonist of the Wnt pathway that induces the rapid disassembly of synapses in mature neurons, and it mediates synaptic loss induced by Aβ (Purro et al, 2012). In HIV-infected subjects, DKK1 levels did differ with NCI (mean 813 pg/ml vs. 549 pg/ml, p < 0.05), particularly in PWH taking ART with HIV RNA levels ≤50 c/ml (Yu et al, 2017). Even if studies are still lacking in HIV, Wnt pathway regulates synaptic transmission and plasticity, and its study could provide a new understanding of some neuropathological processes in the course of HAND.…”
Section: Markers Of Neuronal Damage and Alteration Of Signalingmentioning
confidence: 99%
“…The Dickkopf-related protein 1 (DKK1) is a secreted soluble antagonist of the Wnt pathway that induces the rapid disassembly of synapses in mature neurons, and it mediates synaptic loss induced by Aβ (Purro et al, 2012). In HIV-infected subjects, DKK1 levels did differ with NCI (mean 813 pg/ml vs. 549 pg/ml, p < 0.05), particularly in PWH taking ART with HIV RNA levels ≤50 c/ml (Yu et al, 2017). Even if studies are still lacking in HIV, Wnt pathway regulates synaptic transmission and plasticity, and its study could provide a new understanding of some neuropathological processes in the course of HAND.…”
Section: Markers Of Neuronal Damage and Alteration Of Signalingmentioning
confidence: 99%
“…The activation of the Wnt signaling pathway could promote the occurrence of autoimMune encephalitis ( Schneider et al, 2016 ), and the Wnt signaling pathway was involved in the immunity and tolerance of dendritic cells ( Swafford & Manicassamy, 2015 ). Moreover, plasma Dickkopf-related protein 1, the antagonist of the Wnt signaling pathway, was associated with HIV-related cognitive deficits ( Yu et al, 2017 ). Therefore, KEGG analysis showed that most of the significant clustering pathways were related with the function of the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, plasma Dickkopf-related protein 1, the antagonist of the Wnt signaling pathway, was associated with HIV-related cognitive deficits (Yu et al 2017). Therefore, KEGG analysis showed that most of the significant clustering pathways were related with the function of the nervous system.…”
Section: Discussionmentioning
confidence: 99%